ANALYSIS OF INFORMATION AND ANALYTICAL COMPETENCE IN IMPROVING LIBRARY EDUCATION - Arakelov, Sergey (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2023)
The article analyzes world concepts and foreign experience in creating a new paradigm in the development of information and library education in the digital age. It is proposed to use educational technologies in teaching information and library disciplines, taking into account the analysis of information and analytical competencies, which can change the quality of the process of training highly qualified specialists for information and library institutions of the republic.